2020
DOI: 10.48550/arxiv.2005.12668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SciSight: Combining faceted navigation and research group detection for COVID-19 exploratory scientific search

Abstract: The COVID-19 pandemic has sparked unprecedented mobilization of scientists, already generating thousands of new papers that join a litany of previous biomedical work in related areas. This deluge of information makes it hard for researchers to keep track of their own field, let alone explore new directions. Standard search engines are designed primarily for targeted search and are not geared for discovery or making connections that are not obvious from reading individual papers.In this paper, we present our on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The vastness of COVID-19 literature also spurned the need for having systems that could allow researchers and base users alike to get their COVID-19 queries answered. Systems like CKG (Wise et al) [41] and SciSight (Hope et al) [14] currently provide this functionality. While we do aim to provide an easy to use webframework for medical researchers, the scope of the aforementioned systems is beyond the scope of our work.…”
Section: Related Workmentioning
confidence: 99%
“…The vastness of COVID-19 literature also spurned the need for having systems that could allow researchers and base users alike to get their COVID-19 queries answered. Systems like CKG (Wise et al) [41] and SciSight (Hope et al) [14] currently provide this functionality. While we do aim to provide an easy to use webframework for medical researchers, the scope of the aforementioned systems is beyond the scope of our work.…”
Section: Related Workmentioning
confidence: 99%
“…However, few literature search and recommendation tools address the issue that documents often contain multiple aspects [35]. Further, prior work has also demonstrated that researchers often desire finer-grained control in literature search and navigation tools [12,18,34]. Context-dependent faceted search tools have the potential to fill this gap.…”
Section: Query Titlementioning
confidence: 99%
“…In similar vein Neves et al [34], extensively evaluate a range of methods intended to extract rhetorical structure elements for faceted scientific paper search and evaluate it with a small scale dataset of biomedical publications labelled for fine grained facet similarity. Hope et al [18] allows exploratory search using multi-facet characterizations of scientific articles for the COVID19 research literature. Faceted document similarity for articles has been explored most recently in weakly supervised settings in Ostendorff [35] and Kobayashi et al [22], with both works evaluating using the task of predicting papers cited in a particular section of a research article.…”
Section: Related Workmentioning
confidence: 99%
“…A lot of previous work extracts biomedical entities (Habibi et al, 2017;Crichton et al, 2017;Wang et al, 2018;Beltagy et al, 2019;Alsentzer et al, 2019;Wang et al, 2020c), relations (Uzuner et al, 2011;Krallinger et al, 2011;Manandhar and Yuret, 2013;Bui et al, 2014;Peng et al, 2016;Wei et al, 2015;Peng et al, 2017;Luo et al, 2017;Peng et al, 2019Peng et al, , 2020, and events (Ananiadou et al, 2010;Van Landeghem et al, 2013;Nédellec et al, 2013;Deléger et al, 2016;Li et al, 2019;ShafieiBavani et al, 2020) from biomedical literature, and more recent work focuses on COVID-19 literature (Hope et al, 2020;Ilievski et al, 2020;Wolinski, 2020;Ahamed and Samad, 2020).…”
Section: Related Workmentioning
confidence: 99%